Energy saving solutions for a hydraulic excavator. (September 2017) - Bedotti, Andrea; Campanini, Federico; Pastori, Mirko; Riccò, Luca; Casoli, Paolo
Abstract: Nowadays the improvement of energy efficiency and the reduction of pollutant emissions are the major challenges that the mobile machinery manufacturers have to face with. With rising fuel prices and increasingly stringent regulations, the development of energy saving solutions and efficient hydraulic system have become a priority for researchers and OEM's. One of the most effective approach is the machine hybridization but other solutions can be adopted. This paper proposes with the aid of mathematical tools energy saving solutions for an excavator equipped with a load sensing hydraulic system. A comprehensive energy analysis was conducted through the excavator model to highlight the energy dissipations along the system. Different solutions to reduce losses and improve fuel saving including energy recovery from boom and arm and the introduction of a second pump in the flow generation unit were identified and investigated in detail. Finally, combining the proposed solutions, a new hydraulic hybrid excavator concept was obtained with a 15% of fuel saving.